Juridical Analysis of Transfer of Agricultural Land Functions Into Non-Agricultural Land In The Cilacap Regency - Pridasmara, Bagas Junio (UMPurwokerto Law Review, 2022)
Abstract Cilacap Regency is one area with a relatively large area of land, namely agricultural land. It has a positive impact, namely helping to improve the regional economy, but there is also a negative impact, namely the conversion of agricultural land to non-agriculture. This study aims to determine the conversion of agricultural land into non-agricultural in Cilacap Regency and the obstacles to the transformation of agricultural land. This research used the normative juridical method, which conceptualizes the law as what is written in the legislation. Sources of data in this study used secondary data. The data collection method in this study used a literature study, namely by collecting literature such as books, scientific journals, and primary legal materials to support this research, as well as identification and clarification of legal facts in the field by asking questions to sources that were under this research. Based on the study and discussion results, the conversion of agricultural land to non-agricultural in the Cilacap Regency is not under the Cilacap Regency RTRW. The conversion of agricultural land to non-agricultural land without permission from the local government. It is due to the inhibiting factors consisting of internal factors and external factors. Internal factors are the lack of socialization by the Regional Government regarding the Regional Regulation of Cilacap Regency No. 9 of 2011 concerning the RTRW, and external factors, namely the lack of legal awareness of the community towards the rules for the conversion of agricultural land in Cilacap Regency. Keywords: Transfer of Function, Agricultural Land, Non-agricultural Land Â Abstract Kabupaten Cilacap merupakan salah satu daerah yang memiliki tanah yang cukup luas, yaitu tanah pertanian. Hal ini membawa dampak positif yaitu membantu meningkatkan perekonomian daerah, namun ada juga dampak negatif yaitu alih fungsi tanah pertanian menjadi nonpertanian. Penelitian ini bertujuan untuk mengetahui alih fungsi tanah pertanian menjadi nonpertanian di Kabupaten Cilacap, dan hambatan terhadap alih fungsi tanah pertanian tersebut. Metode yang digunakan dalam penelitian ini adalah yuridis normatif, dimana hukum dikonsepkan sebagai apa yang tertulis di peraturan perundang-undangan. Sumber data dalam penelitian ini menggunakan data sekunder. Metode pengumpulan data dalam penelitian ini menggunakan studi kepustakaan yakni dengan mengumpulkan literatur seperti buku-buku, jurnal ilmiah, dan bahan hukum primer untuk mendukung penelitian ini serta identifikasi dan klarifikasi fakta hukum di lapangan dengan cara mengajukan pertanyaan kepada narasumber yang sesuai dengan penelitian ini. Berdasarkan hasil penelitian dan pembahasan, alih fungsi tanah pertanian menjadi nonpertanian di Kabupaten Cilacap ada yang belum sesuai dengan RTRTW Kabupaten Cilacap, yaitu adanya alih fungsi tanah pertanian menjadi nonpertanian tanpa izin dari pemerintah daerah. Hal itu dikarenakan adanya faktor penghambat yang terdiri dari faktor internal dan faktor eksternal. Faktor internal yakni kurangnya sosialisasi yang dilakukan oleh Pemerintah Daerah tentang Perda Kabupaten Cilacap No.9 Tahun 2011 tentang RTRW dan faktor eksternal yaitu kurangnya kesadaran hukum masyarakat terhadap aturan alih fungsi tanah pertanian di Kabupaten Cilacap. Kata kunci: Alih Fungsi, Tanah Pertanian, Tanah NonpertanianÂ